Perioperative Transcutaneous Electrical Acupoint Stimulation Reduces Postoperative Pain in Patients Undergoing Thoracoscopic Surgery: A Randomized Controlled Trial - Jianming Liu; Keqin Zhang; Yongyan Zhang; Feng Ji; Haifeng Shi; Yi Lou; Hua Xu (Pain Research and Management)
Objectives. This study aimed to determine the effects of perioperative transcutaneous electrical acupoint stimulation (TEAS) on postoperative pain management in patients undergoing thoracic surgery. Methods. In the prospective, randomized, controlled study, a total of 84 patients undergoing video-assisted thoracoscopic surgery (VATS) were randomly allocated to the TEAS group (Group T) or control group (Group C). Patients in the Group T received TEAS at Neiguan (PC6) and Hegu (LI4) acupoints for 30 min before anesthesia induction and 30 min after thoracoscopic surgery. Patients in the Group C received the same placement of electrodes but without electrical stimulation. The numeric rating scale (NRS) pain score, remifentanil consumption, demand for rescue analgesics and incidence of postoperative nausea and vomiting (PONV), patient satisfaction, and the levels of plasma β-endorphin (EP) and IL-6 were recorded. Results. Patients in the Group T had significantly lower NRS pain scores at 6 h, 12 h, 24 h, and 48 h after surgery than those in the Group C. Compared with Group C, patients in Group T had lower remifentanil consumption during operation, lower demand for rescue analgesics and lower rate of PONV within 24 h after surgery. Patients in Group T also had lower IL-6 content, higher β-EP content and higher satisfaction degree than those in the Group C. Conclusions. Perioperative TEAS significantly decreased postoperative pain and rescued analgesia requirements and the incidence of PONV in patients undergoing thoracoscopic surgery, with a higher patient satisfaction. This trial is registered with ChiCTR2100051841.